2018
DOI: 10.3340/jkns.2018.0057
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancement of the Molecular Diagnosis in Pediatric Brain Tumor

Abstract: Recent discoveries of brain tumor-related genes and fast advances in genomic testing technologies have led to the era of molecular diagnosis of brain tumor. Molecular profiling of brain tumor became the significant step in the diagnosis, the prediction of prognosis and the treatment of brain tumor. Because traditional molecular testing methods have limitations in time and cost for multiple gene tests, next-generation sequencing technologies are rapidly introduced into clinical practice. Targeted sequencing pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…This knowledge is essential for developing personalized treatment strategies and improving patient outcomes. The inclusion of molecular markers has in fact improved diagnostic accuracy and allowed the development of targeted therapies based on genetic anomalies of specific tumor types [137]. Therapies for CNS tumors may include surgery, radiation therapy, chemotherapy, targeted therapies, and immunotherapy in a multidisciplinary approach [138,139].…”
Section: Central Nervous System Tumoursmentioning
confidence: 99%
“…This knowledge is essential for developing personalized treatment strategies and improving patient outcomes. The inclusion of molecular markers has in fact improved diagnostic accuracy and allowed the development of targeted therapies based on genetic anomalies of specific tumor types [137]. Therapies for CNS tumors may include surgery, radiation therapy, chemotherapy, targeted therapies, and immunotherapy in a multidisciplinary approach [138,139].…”
Section: Central Nervous System Tumoursmentioning
confidence: 99%
“…Pharmacological high-throughput drug screening is readily applied to identify and evaluate potential therapeutics [29]. Moreover, diagnostically, the use of high-throughput omic analysis showed that molecular signatures of pediatric CNS tumors better predict patient outcome compared to histopathology alone [37,38,39,40,41].…”
Section: Applications To the Clinic: The Good The Bad And The Uglymentioning
confidence: 99%